Arrival of fish products in the morning - Mumbai Archive Project Team (Jio Institute, 2024)
The catch arrives in the morning and is immediately preserved in ice boxes to maintain flavour and freshness. This fish includes Koli specialties like Bombay duck (bombil), pomfret (paplet), mackerel (bangda), sardines (tarli, pedvey), king fish (surmai), golden anchovy (mandeli), prawns (kolambi), and shrimp (jhinga).